2020
DOI: 10.1124/molpharm.120.000054
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacology and Molecular Mechanisms of Clinically Relevant Estrogen Estetrol and Estrogen Mimic BMI-135 for the Treatment of Endocrine-Resistant Breast Cancer

Abstract: Long-term estrogen deprivation (LTED) with tamoxifen (TAM) or aromatase inhibitors leads to endocrine-resistance, whereby physiologic levels of estrogen kill breast cancer (BC). Estrogen therapy is effective in treating patients with advanced BC after resistance to TAM and aromatase inhibitors develops. This therapeutic effect is attributed to estrogen-induced apoptosis via the estrogen receptor (ER). Estrogen therapy can have unpleasant gynecologic and nongynecologic adverse events. Here, we study estetrol (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 73 publications
(93 reference statements)
0
27
0
1
Order By: Relevance
“…A possible explanation for this data is that diminished genomic activation of both ER and AR may be more permissive of non-canonical pathways. The reduced production of potent sex steroids, accompanied by a surfeit of weak precursor steroids in aging adults provides rationale for the benefit of therapeutic agents that drive genomic nuclear receptor activity (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this data is that diminished genomic activation of both ER and AR may be more permissive of non-canonical pathways. The reduced production of potent sex steroids, accompanied by a surfeit of weak precursor steroids in aging adults provides rationale for the benefit of therapeutic agents that drive genomic nuclear receptor activity (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Estetrol (E4) has shown such a pattern [ 118 ]: this agent is less potent than E2 and shows some tissue selectivity as it induces limited effects on the liver [ 119 ]. E4 is under clinical development for a few indications including contraception and breast cancer [ 120 , 121 ].…”
Section: Intricacies Of Er Pharmacological Modulationmentioning
confidence: 99%
“…In in vitro experiments performed on a long-term estrogen-deprived (LTED) human MCF7 breast cancer cell line [63] and in endocrine-resistant ER + breast cancer cells [61] E4 had pro-apoptotic properties similar to E2. In endocrine-resistant ER + breast cancer cells, these pro-apoptotic properties were associated with an ERα-dependent UPR [61]. Singer et al [64], reported that when E4 was administrated orally (20 mg/day) for 2 weeks in women with recently diagnosed breast cancer, immunohistochemical assessment of tumors revealed an increased number of apoptotic cells but no modulation of the proliferative marker Ki67, when compared to placebo.…”
Section: Estetrol and Breast Cancermentioning
confidence: 99%
“…However, there is a reluctance to use E2 due to the potential for adverse effects, especially thromboembolism [99][100][101][102][103][104]. The pro-apoptotic properties of E4 on endocrine-resistant breast cancer demonstrated in vitro [61] and in clinical trials [64,65], in addition to the limited effect of E4 on liver factors involved in coagulation [79], support a potential role for E4 in the treatment of advanced endocrine-resistant breast cancer in postmenopausal women.…”
Section: Breast Cancer Treatmentmentioning
confidence: 99%